Analisis Keterbacaan Buku “Sabar” Menggunakan Teori Fog Index - Novianto, Syam Anis; Abdurrahman, Maman; Supriadi, Rinaldi (Borneo Journal of Language and Education, 2024)
One of the learning resources used in the learning process at school is instructional books or textbooks. The difficulties in textbooks will be felt by students as textbook users if the language aspects used in the book are quite complicated or difficult. So this research aims to discuss the readability level of discourse in an Arabic language textbook for class X SMA/SMK semester 1 based on the Fog Index readability formula. The method used is descriptive qualitative. Data was collected using documentation techniques and questionnaires regarding the discourse in the book. This research begins with defining textbooks and their readability, then analyzing the readability level of three discourses in the book "SABAR" using Fog Index theory. The results of the research show that the readability level of the discourse in the textbook is classified as 'very easy' to read with the results for the 1st discourse being 1.92, then the 2nd discourse being 1.6 and the 3rd discourse being 1.57. Then the average of the calculations for the three discourses in the book is 1.7. Thus, the textbook falls into the calculation of less than 3, which means the book falls into the category of very easy to read and is not ideal for learning activities because based on average it is very easy, so it can cause students to get bored quickly. The results of the questionnaire show that the higher the level, the number of difficult words also get higher, such as in the 1st discourse there are 36 difficult words, then in the 2nd discourse there are 38 difficult words, and in the 3rd discourse there are are 44 difficult words. The percentage of difficult words from all discourses is 53% of all words, but the length of sentences in each discourse does not increase in number.